Spatio-Temporal Differentiation Characteristic and Evolution Process of Meteorological Drought in Northwest China From 1960 to 2018 - Li, Hui; Hou, Enke; Deng, Jiawei (Frontiers in Earth Science, 2022)
Against the backdrop of global climate change, the response characteristic of meteorological drought is of great concern, especially in the arid or semi-arid regions. By employing the Standardized Precipitation Index (SPI), TPFW-MK test, Run Theory, Moran’s I, and General G, the spatio-temporal evolution characteristic of drought was clarified and the spatial autocorrelation of local and global drought characteristic variables was explored based on the meteorological data from 122 stations in Northwest China (NWC) during 1960–2018. The results indicated that the drought situation of NWC was improving regardless of annual or seasonal scale. According to the Z-statistics by the TPFW-MK test, there existed an obvious wet trend in west NWC and a slight dry trend in east NWC. The center of gravity migration model revealed that the gravity center of SPI moved towards higher latitude over the last decades, there was a northwest (1960–1990) and northeast (1990–2018) variation in the covering shapes of the standard deviational ellipses of SPI, and the spatial distribution of SPI tended to be concentrated. Meanwhile, the distribution pattern of drought characteristics suggested that more droughts occurred in east of NWC, which were less harmful while fewer droughts happened in west NWC, which brought greater drought damage. The results of global Moran’s I (GMI) indicated that both annual and seasonal drought variables were characterized with significant spatial autocorrelation, the spatial distribution of winter drought variables was more disperse than other seasons, while the damage of summer and autumn drought was bigger than that in spring and winter. Besides, the results of local Moran’s I (LMI) showed that there was obvious agglomeration in the overall distribution of drought characteristic variables, which had a seesaw effect. The spatial distribution of hot spots and cold spots at different confidence levels indicated that Shaanxi Province experienced the most droughts but with shortest duration and lowest severity while northwest Xinjiang had the fewest droughts with longest duration and highest severity. The results of revealing the drought development process and identifying the location of drought aggregation will provide references for supporting climate adaptation strategies and preventing drought-related loss.